Comparison of Physicochemical Attributes of Einkorn Wheat (Triticum monococcum) and Durum Wheat (Triticum durum) and Evaluation of Morphological Properties Using Scanning Electron Microscopy and Image Analysis - Ertop, Müge Hendek; Atasoy, Rabia (Ankara University Faculty of Agriculture, 2019)
Einkorn (Triticum monococcum L. subsp. monococcum) is a diploid hulled wheat strictly related to durum and bread wheat types. Many farms in northern Turkey, especially the province of Kastamonu, continue to cultivate the oldest type of wheat still in existence, Triticum monococcum, also known as Siyez. Although there is great potential for breeding, it’s production and consumption has been locally limited and cultivation quantity has been very low. However nowadays, today’s consumer demands to traditional or regional food products and grains have been increased einkorn cultivation in Kastamonu, and cultivation area has been reached to approximately from 5 thousand decares to 35 thousand decares. Einkorn is cultivated two times a year in Kastamonu. The variety which is named as “Çatal Siyez” (Kaplica) composed 60-70% of the production of einkorn, is sowed in April and used as animal feed after harvest. Another type which is “Tek Siyez” variety sowed in October is processed to produce einkorn flour and bulgur. In this study, some physicochemical attributes of Einkorn (Triticum monococcum) and Durum Wheat (Triticum durum) were compared and their morphological properties were evaluated by using scanning electron microscopy and image analysis. The scanning electron microscopy micrographs shown that Einkorn had opaque but durum wheat had a vitreous appearance. In addition, the starch granules could be easily separated visually in Einkorn texture. In durum wheat, the protein bonds were more compact and the diameter of starch granules located in protein matrix lower than ones of Einkorn. Moreover, it was determined that visually the caryopsis layers of Einkorn were thinner than ones of the durum wheat. The kernel weight (g 1000 pieces-1) of Einkorn was found lower (27.94 g) than durum wheat (54.6 g). Also, water absorption was 51.8% of Einkorn and 65.3% of durum wheat. The ash, protein, fat content and antioxidant activity of Einkorn sample were determined higher than durum wheat. Mineral content of the samples was analyzed, and Einkorn contained higher amount of trace and major elements especially in terms of Zn, Fe and Al. The results show that many foods will able to fortified by einkorn or einkorn products such as semolina, flour, germ or bulgur as a solution of micronutrient malnutrition problem, and to meet todays consumers demand which are cleanlabel and additive-free food. Moreover, einkorn is a promising candidate for the development of new or special foods such as bakery products, baby food or products with high content of dietary fiber, protein, minerals, carotenoids and tocols.
Keywords: Triticum monococcum; Agriculture (General); Mühendislik; durum wheat; Siyez; einkorn; Triticum monococcum; durum wheat; image analys; Einkorn; triticum monococcum; image analys; S1-972; Engineering; einkorn; siyez; Siyez; 2. Zero hunger